Elucidating tricuspid Doppler signal interpolation and its implication for assessing pulmonary hypertension. (22nd August 2022) - Dual, Seraina A.; Verdonk, Constance; Amsallem, Myriam; Pham, Jonathan; Obasohan, Courtney; Nataf, Patrick; McElhinney, Doff B.; Arunamata, Alisa; Kuznetsova, Tatiana; Zamanian, Roham; Feinstein, Jeffrey A.; Marsden, Alison; et al.
Abstract: Doppler echocardiography plays a central role in the assessment of pulmonary hypertension (PAH). We aim to improve quality assessment of systolic pulmonary arterial pressure (SPAP) by applying a cubic polynomial interpolation to digitized tricuspid regurgitation (TR) waveforms. Patients with PAH and advanced lung disease were divided into three cohorts: a derivation cohort ( n = 44), a validation cohort ( n = 71), an outlier cohort ( n = 26), and a non‐PAH cohort ( n = 44). We digitized TR waveforms and analyzed normalized duration, skewness, kurtosis, and first and second derivatives of pressure. Cubic polynomial interpolation was applied to three physiology‐driven phases: the isovolumic phase, ejection phase, and "shoulder" point phase. Coefficients of determination and a Bland−Altman analysis was used to assess bias between methods. The cubic polynomial interpolation of the TR waveform correlated strongly with expert read right ventricular systolic pressure (RVSP) with R 2 > 0.910 in the validation cohort. The biases when compared to invasive SPAP measured within 24 h were 6.03 [4.33; 7.73], −2.94 [1.47; 4.41], and −3.11 [−4.52; −1.71] mmHg, for isovolumic, ejection, and shoulder point interpolations, respectively. In the outlier cohort with more than 30% difference between echocardiographic estimates and invasive SPAP, cubic polynomial interpolation significantly reduced underestimation of RVSP. Cubic polynomial interpolation of the TR waveform based on isovolumic or early ejection phase may improve RVSP estimates.